Coping with brackish water: A new species of cave-dwelling Protosuberites (Porifera: Demospongiae: Suberitidae) from the Western Mediterranean and a first contribution to the phylogenetic relationships within the genus - Melis, P.; Riesgo, A.; Taboada, S.; Manconi, R. (Zootaxa, 2016)
We used both morphological and genetic approaches to investigate and to describe a new Mediterranean sponge species of the genus Protosuberites from the estuarine-anchialine Bue Marino Cave of Sardinia (Tyrrhenian Sea). The morphotraits of the specimens were compared versus congeneric species with the strongest affinities, covering the genus geographic range worldwide. Protosuberites mereui sp. nov. is light yellow, thinly encrusting, devoid of any special ectosomal skeleton, with spicular complement of tylostyles of three size classes, single or arranged in bundles/tufts, with round to suboval heads. The new species is characterized by an exclusive diagnostic trait recorded for any cave-dwelling Protosuberites i.e. suboval and basally plated resting bodies with a foraminal aperture ornate by a collar. Resting bodies were found in the basal spongin plate firmly adhering to the substratum singly or in small groups. Also the rare, small tylostyles with a sinuous shaft and a typical mushroom-like head were never recorded in the Western Mediterranean and Atlantic species of the genus. The phylogenetic reconstruction using maximum likelihood (ML) and Bayesian Inference (BI) analyses (COI, 18S rRNA, and 28S rRNA) recovered a robustly supported sister relationship between the Mediterranean P. mereui sp. nov. and Protosuberites sp. ‘Panama’ from the Eastern Pacific Ocean. The genetic distances based on COI sequences between all compared Protosuberites species were always higher than 2%, a value sufficient to confirm that P. mereui sp. nov. is a distinct species within the genus. Morphological and genetic analyses confirm unanimously P. mereui sp. nov. as a new species. Our results contribute to the assessment of biodiversity in anchialine/estuarine caves and increase data on sponge adaptive strategies in these extreme ecosystems.